2001
DOI: 10.2165/00003495-200161120-00004
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen Resistance in Breast Cancer

Abstract: Tamoxifen has been used for the systemic treatment of patients with breast cancer for nearly three decades. Treatment success is primarily dependent on the presence of the estrogen receptor (ER) in the breast carcinoma. While about half of patients with advanced ER-positive disease immediately fail to respond to tamoxifen, in the responding patients the disease ultimately progresses to a resistant phenotype. The possible causes for intrinsic and acquired resistance have been attributed to the pharmacology of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(63 citation statements)
references
References 128 publications
1
61
0
1
Order By: Relevance
“…BCAR1, which encodes p130CAS, is upregulated in breast tumours resistant to tamoxifen 121,122 . Consistently, the over-expression of p130CAS in breast cancer cells induces proliferative signals that are not sensitive to treatment with either tamoxifen or oestrogen receptor antagonist fulvestrant 121,123 . Although it has been reported that a possible mechanism through which p130CAS induces tamoxifen resistance is its binding to BCAR3/AND34, a putative GEF for RALA, RAP, and RRAS GTPases 124 , the exact mechanism by which p130CAS and BCAR3 induce anti-oestrogen resistance remains unclear.…”
Section: Clinical Implications Of Integrin Adaptorsmentioning
confidence: 67%
“…BCAR1, which encodes p130CAS, is upregulated in breast tumours resistant to tamoxifen 121,122 . Consistently, the over-expression of p130CAS in breast cancer cells induces proliferative signals that are not sensitive to treatment with either tamoxifen or oestrogen receptor antagonist fulvestrant 121,123 . Although it has been reported that a possible mechanism through which p130CAS induces tamoxifen resistance is its binding to BCAR3/AND34, a putative GEF for RALA, RAP, and RRAS GTPases 124 , the exact mechanism by which p130CAS and BCAR3 induce anti-oestrogen resistance remains unclear.…”
Section: Clinical Implications Of Integrin Adaptorsmentioning
confidence: 67%
“…In addition, in the absence of oxygen, P450 reductase interacts with anthracyclines, leading to cleavage of the anthracycline glycosidic bond and producing a molecule with no antitumour activity (Pan et al, 1981). In the CMF-treated group, most patients also received TAM concomitantly, which could have counterbalanced the cytotoxic resistance induced by hypoxia at least in part since the drug induces apoptosis that is ER mediated (Dorssers et al, 2001) and may not be influenced by tumour oxygenation. It has been demonstrated that the oxygenation status of human tumours is independent of clinical tumour size stage and grade (Wouters et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…These observations highlight the fact that different mechanisms for TR are likely and may involve adaptive changes as well as 'antiestrogen resistance genes'. Perhaps breast tumors in carriers of so called 'antiestrogen resistance genes' (Dorssers et al 2001) 274 www.endocrinology.org have a lesser ability to modulate MAPK and aromatase as adaptive processes than those with 'adaptive TR'.…”
Section: Discussionmentioning
confidence: 99%